Polyvagal and Global Cytokine Theory of Safety and Threat Covid-19 - Plan B - David Hanscom; David Roger Clawson; Stephen W. Porges; Ray Bunnage; Les Aria; Steve Lederman; James Taylor; C. Sue Carter (Ital Publication, 2020)
We are presenting this document to medical providers as a systematic approach to improve outcomes of patients with COVID-19. The following variables are considered: Autonomic nervous system viewed from the perspective of the Polyvagal Theory; Timing of interventions in terms of phase of the body's defense (Fight, Flight, Freeze, Faint); The nervous system considered the context of a "One System" perspective; Protein/Enzyme function; Immune system; Cytokine load - activity, inflammation and metabolic response; Viral load; Angiotensin 2 load. The ARDS and multi-system organ failure of the COVID-19 is a complex problem. This approach acknowledges the complexity and presents a structure where the variables are systematically addressed. 1. The common risk factors for death are associated with baseline elevations of pro-inflammatory cytokines. Measures can be taken to lower them before being exposed to the virus-Plan A. 2. Strategies to optimize the body's defenses should be assessed and optimized. These include nutrition, vitamins, and trace elements, sleep, exercise, and minimizing threat. 3. The body's own resources are utilized through recruiting the autonomic nervous system to counteract elevated pro-inflammatory cytokines. The interventions are implemented in the context of what stage of defense the body is in-fight, flight, freeze, or faint. 4. Progressive pharmacological interventions are considered with the early interventions being those with minimal risk. We are asking the following: • This approach is viewed as the foundation for clinical interventions. They should be implemented in a systematic and stepwise manner. • Most of the treatments are already medically proven with minimal or no risk. • All basic treatments are in place before more aggressive interventions are implemented. • That this process be considered a framework to test clinical protocols and novel therapies. Much work needs to be done regarding dosing and timing. • We are particularly interested in the potential of the following interventions, which do need to be looked at in a protocol.• o Allowing ketosis in the Mid and Late Phases of the illness. • o Considering the use of ketone bodies instead of glucose for fuel in Mid and Late Phases of illness. • o Eliminating glucocorticosteroids in the Early and Mid-Phases the use of steroids. • o Utilizing the anti-inflammatory cholinergic nervous system (vagal stimulation, nicotine patches, etc.). • o Closer monitoring of IL-6 to in real time deliver the most appropriate interventions.   Doi: 10.28991/SciMedJ-2020-02-SI-2 Full Text: PDF